Sandwich technique for endovascular repair of type A aortic dissection following stent graft with an inner branch in the ascending aorta - Kosuke Ujihira, MD; Reiko Kemmochi, MD; Taiichiro Matsumoto, MD; Noriyuki Tokunaga, MD, PhD; Mitsuaki Matsumoto, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
Type A aortic dissection after thoracic endovascular aortic repair is a life-threatening complication. We present a case of acute type A aortic dissection that occurred after zone 0 stent grafting with a physician-modified inner branch in the ascending aorta. We performed additional endovascular aortic repair using the sandwich technique, which involved placing a chimney stent graft for the brachiocephalic artery and a main aortic stent graft covered by a shortened outer stent graft in the ascending aorta. This technique minimized device diameter, preventing over-dilatation of the true lumen, with sufficient overlap of the stent grafts.